Characteristics of Biscuit Substituted with of Mocaf (Modified Cassava) and Soya Flour (Glycine max) With The Addition of Cinnamon (Cinnamomum burmanii)an Kayu Manis (Cinnamomum burmanii) - Indah Tri Hartati; Nanik Suhartatik; Irvia Resti Puyanda (Fakultas Sains dan Teknologi Unisri, 2026)
Biscuits are a dry food product made by baking dough made from wheat flour and additional food ingredients. The increasing consumption of wheat flour needs to be reduced gradually, namely by alternative use of other flours such as mocaf and soybean flour which can be used as an altenative and increase nutritional value as a source of protein. The aim of this research was to find out the biscuit formulations that consumers like the most and to determine the chemical and organoleptic characteristics of biscuits that are high in protein and antioxidants. This research begins with making cinnamon powder, namely sorting, grinding, and sieving. The process of making biscuits includes weighing, mixing, cutting off and baking. This research used a Completely Randomized Design (CRD) with two factors, namely the ratio of wheat flour, soy flour, and mocaf (2:1:17, 2:2:16, 2:3:15) and the percentage of cinnamon powder (5%, 10%, 15%). The data analysis collection techniques used descriptive analysis, ANOVA test and Duncan test. The parameters observed in this research include analysis of water, ash, fat, protein, carbohydrates, antioxidant activity, and organoleptic tests using the scoring test method. The research results showed that the biscuit formulation was high in protein and antioxidants and was also liked by the panelists found in the formulation, 2 part of wheat flour: 3 part of soybean flour: and 15 part of mocaf and 15% of cinnamon powder. The products have 6.65% for protein and antioxidant activity 85.96 % with the highest organoleptics score of biscuit brown color 3.65, cinnamon aroma 3.31, crisp texture 3.81 and cinnamon taste 3.17. Soy flour addition could increase the protein of biscuit.